Konsep Terikat Dan Terlepas Dalam Matius 16: 19 Dan Implikasinya Bagi Pemimpin Gereja - Muryati Muryati Muryati; Melvin Abrillian; Purim Marbun; Yusak Setianto (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
Authority is always attached to a leader, including church leaders. However, the problem is that there are some leaders who abuse authority for their own interests. There are also other leaders who cannot use an authority in determining doctrinal and ethical matters. Therefore, this study aims to explain the authority of the disciples to bind and release the law in Matthew 16:19 and its implications for today's church leaders. This research method is qualitative with a hermeneutic approach based on a literature study. The results of the study show that the authority was given by God to expand His kingdom on earth so church leaders must use this gift for His glory and improve the quality of the congregation that God has entrusted to him.